Parangtritis multi obyek wisata / Suwarno, Suprihatin, dan I Wayan Dana; editor, Iman Budi Santosa - SUWARNO; Suprihatin; I Wayan Dana; Iman Budi Santosa (Lembah Manah, 2012)
xi, 142 hlm. : ilus. ; 21 cm.